The role of back stress in sub-50 nm Si nanocubes. (15th March 2016) - Hintsala, E.D.; Wagner, A.J.; Gerberich, W.W.; Mkhoyan, K.A.
Abstract: Development of more accurate descriptions of dislocation motion requires understanding the actual effective stress driving it. Back stresses from dislocation pile-ups can work against the applied stress resulting in lower stresses acting on moving dislocations. This study presents calculations of back stress derived from in-situ compression of 26–39 nm sized single crystal silicon cubes inside the transmission electron microscope. These initially dislocation free particles exhibited yielding culminating in over 60% plastic strain. The back stress was calculated based on a pile-up model which, when subtracted from the applied stress, suggests a constant effective stress for continuing plasticity. Graphical abstract: